Exploring the challenges of engaging in entrepreneurial activities among undergraduate students: a case study in Malacca / Wan Aisyah Amni Wan Mohamad Saferdin … [et al.] - Wan Mohamad Saferdin, Wan Aisyah Amni; Abu Karim, Rizuwan; Mohd Nor, Khalijah; Mohd Kodri, Aida Nur; Ahmad, Siti Nurul Akma; Muhamad Hanapiyah, Zulkefli (2023)
In academic research, many studies are done to highlight issues faced during business start-ups, like limited resources among young entrepreneurs. However, very few studies were conducted to determine challenges faced undergraduate entrepreneurs. Students who have involves themselves in entrepreneurship at their universities have indeed gone through challenge along the way. Thus, the aim of this study is to explore the challenges of engaging in entrepreneurial activities among undergraduate students in Malacca. The qualitative research method was used in this study. The information was gathered through semi-structured interviews. The interview session included 15 undergraduate students at a Malaysian public university in Malacca as a sample of study. The interview transcripts were analysed using thematic analysis (TA). The results of this study have identified a number of challenges encountered by undergraduate students as they engage in entrepreneurship. Knowledge, financial, time, facility, location, competition and mentoring are challenges encountered by undergraduate’s students while doing entrepreneurship activities. This finding is expected to contributes to economic growth and innovation within the region, as entrepreneurial ventures often lead to job creation and the development of new products and services. This study serves as a guideline for educational institutions, government agencies, industry stakeholders to provide a sustainable mechanism and strategy for future entrepreneurial activities in higher education institutions.